Recent discoveries of Aurignacian and Epigravettian sites in Albania. (3rd March 2016) - Hauck, Thomas C.; Ruka, Rudenc; Gjipali, Ilir; Richter, Jürgen; Vogels, Oliver
Abstract : Albania is a possible stepping-stone for the dispersal of Homo sapiens into Europe, since Palaeolithic traces (namely from the so-called Uluzzian culture) have been discovered in neighboring Greece and Italy. After two years of searching for evidence of modern humans in Albania we here report on excavated test trenches representing two time slices: an Aurignacian open-air site from southern Albania and two Epigravettian cave sites in central and northern Albania—areas heretofore archaeologically unknown. The new Albanian data fill a gap in the eastern Adriatic archaeological record for Marine Isotope Stages 3 and 2. Adding current knowledge of Late Pleistocene landscape evolution, a "contextual area model" can be constructed describing the habitats of these human populations.